Outcomes and change processes of an established family education program for carers of adults diagnosed with a serious mental health condition. Issue 7 (29th May 2020) - Farhall, John; Cugnetto, Marilyn L.; Mathews, Stephanie; Ratcliff, Kirk; Farnan, Sue; Higgins, Kate; Constantine, Emma
Abstract: Background: Family education programs (FEPs) target caregiving-related psychological distress for carers of relatives/friends diagnosed with serious mental health conditions. While FEPs are efficacious in reducing distress, the mechanisms are not fully known. Peer group support and greater mental health knowledge are proposed to reduce carers' psychological distress by reducing stigmatising attitudes and self-blame, and strengthening carers' relationship with their relative. Methods: Adult carers ( n = 1016) who participated in Wellways Australia's FEP from 2009 to 2016 completed self-report questionnaires at the core program's start and end, during the consolidation period, and at a 6-month follow-up. Those who enrolled early completed questionnaires prior to a wait-list period. We used linear mixed-effects modelling to assess the program's effectiveness using a naturalistic wait-list control longitudinal design, and multivariate latent growth modelling to test a theory-based process change model. Results: While there was no significant change over the wait-list period, psychological distress, self-blame and stigmatising attitudes significantly decreased, and communication and relationship quality/feelings increased from the core program's start to its end. Changes were maintained throughout the consolidation period and follow-up. Peer group support significantly predicted the declining trajectory of distress. Peer group support and greater knowledge significantly predicted declining levels of self-blame and stigmatising attitudes, and increasing levels of communication. Conclusions: This is the first study to quantitatively validate the mechanisms underlying the effect of FEPs on carers' psychological distress. Peer group support is key in modifying carers' appraisals of their friend/relatives' condition. Continued implementation of FEPs within mental health service systems is warranted.